"Less than a Vapor": Positioning Black lesbian women in history teacher education. Issue 4 (2nd October 2017) - Woodson, Ashley N.
ABSTRACT: In this article, I discuss the possibilities and implications of centering Black lesbian identities and relationships in history teacher education through a case study with one straight Black woman preservice history teacher named Danitra. Danitra's understanding and navigation of historical research on Black lesbians are discussed in relation to core themes of lesbian historiography and emancipatory historiography . Though the literature on this group is limited, I argue that critical considerations of Black lesbians' interests and experiences help educators to conceive of and teach about history, citizenship, justice, and sexuality in more liberatory ways. I conclude by offering recommendations to history teachers and teacher educators who hope to draw on lesbian and emancipatory historiographies to challenge discourses of invisibility in history teacher education classrooms.